Genetic Studies of Stevioside Content and Other Agronomic Characters and Their Responses to Cloning in Stevia Rebaudiana Bert. - Wong, Lock Jam (1991)
Stevia rebaudiana Bert. produce s the sweetener stevioside, which is 300 times sweeter than cane sugar. However, the Mean stevioside content of commercial cultivars was gene rally low and among the better cultivars the average stevioside content was in the region of seven percent. Studies were set up to investigate the genetic system temofstevio side content and other traits, the effects of cloning and the relationship of stevioside content to the other traits. Three segregating population, where up on 18 lines were selected for studying the effects of cloning.